2020
DOI: 10.1002/ajmg.a.61486
|View full text |Cite
|
Sign up to set email alerts
|

Missense variants in the Arg206 residue of HNRNPH2: Further evidence of causality and expansion of the phenotype

Abstract: Missense variants in HNRNPH2 cause Bain type syndromic X‐linked intellectual disability (XLID). To date, only six affected females and three affected males have been reported in the literature, and the phenotype has yet to be delineated in detail. Here, we report on a 35‐year‐old female with a novel de novo variant in HNRNPH2, providing further evidence that missense changes in the nuclear localization sequence cause Bain type XLID and that aminoacid 206 likely represents a mutational hotspot. We expand the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Stereotypies can be present, not necessarily in the context of autism. Brain MRI can be significant for cerebellar vermis hypoplasia and subcortical atrophy [71,72]. Severe ID with abnormal tone, absent speech and ataxic gait can suggest RTT, although the main clinical features are absent, including regression (documented once, at 20 years of age, in a patient without epilepsy), and abnormal development is detectable since the first months of life.…”
Section: Transcription Regulation/modification Hnrnph2mentioning
confidence: 99%
See 1 more Smart Citation
“…Stereotypies can be present, not necessarily in the context of autism. Brain MRI can be significant for cerebellar vermis hypoplasia and subcortical atrophy [71,72]. Severe ID with abnormal tone, absent speech and ataxic gait can suggest RTT, although the main clinical features are absent, including regression (documented once, at 20 years of age, in a patient without epilepsy), and abnormal development is detectable since the first months of life.…”
Section: Transcription Regulation/modification Hnrnph2mentioning
confidence: 99%
“…However, during disease course, the association of stereotypies with breathing and sleep disruption can lead to a diagnosis of an RTT-like phenotype. Of note, adultonset oro-mandibular dystonia (at 19 years) and tremor (since age 31 years) have been described [72].…”
Section: Transcription Regulation/modification Hnrnph2mentioning
confidence: 99%
“…In addition to our studies implicating HNRNPH1 in processing the oncogenic fusion transcripts expressed in a subset of Ewing sarcomas, several recent reports have described disease-associated sequence changes in HNRNPH/F genes. For example, multiple reports have linked mutations in HNRNPH1 or HNRNPH2 to rare neurodevelopmental syndromes that exhibit variations in phenotype but include dysmorphic features and intellectual disability (24)(25)(26)(27)(28)(29)(30). The described mutations include missense mutations, frameshift and in-frame deletions, and partial gene duplications (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…The HNRNPH2-related disorder is characterized by global developmental delay, intellectual disability, behavioral and psychiatric issues, cerebellar hypoplasia, ataxia, seizures, and dysmorphic features (Bain et al, 2016). Additional features include musculoskeletal abnormalities, such as hypotonia and joint laxity, as well as acquired microcephaly and feeding problems with poor overall growth (Peron et al, 2020). Bain et al (2016) first reported six unrelated females who all carried de novo missense variants in HNRNPH2 (MIM: 300610) five of which were located at amino acid position 206 and a sixth de novo variant located at the nearby amino acid position 209.…”
mentioning
confidence: 99%
“…However, authors have previously hypothesized skewed X-inactivation in females as a mechanism to explain the range of neurological phenotypic severity in females with HNRNPH2-related disorder (Bain et al, 2016;Peron et al, 2020). X-inactivation analysis of the proband's mother was therefore performed and showed skewed X-chromosome inactivation by a ratio of 1:99 (Hospital for Sick Children Genome Diagnostics Laboratory, 2021).…”
mentioning
confidence: 99%